Evaluating flourishing: a comparative analysis of four measures using item pool visualization - Ploke, Veronika; Batinic, Bernad; Stieger, Stefan (Frontiers in Psychology, 2024)
The construct of flourishing, which refers to a high level of wellbeing, is a key concept in the field of positive psychology. Nevertheless, despite the proliferation of questionnaires attempting to measure wellbeing and flourishing, there is still an ongoing debate in the scientific community about the definition and assessment of both, which makes the choice of appropriate measures a major challenge. This study addresses this uncertainty through a comparative analysis of four widely used flourishing measures in a German-speaking sample, to enable researchers to make a reasonable choice among the measures available: the PERMA-Profiler, the Mental Health Continuum-Short Form, the Flourishing Scale, and the Wellbeing Conceptual Framework. To enhance the understanding of these four measures, we compared and contrasted the instruments using Item Pool Visualization (IPV), an illustrative approach that generates item pools from the same dataset and displays them as nested radar maps. Our research indicates that all four measures are useful in measuring the concept of flourishing. However, they differ from each other depending on specific interest (from a broader to a narrower view). If the aim is to get a comprehensive overview of flourishing, then the PERMA-Profiler, the Mental Health Continuum-Short Form, and the Flourishing Scale are appropriate options. If the focus is on measuring a more central concept, the Wellbeing Conceptual Framework provides the most specific assessment of flourishing.